How Do Entrepreneurship And Spillover Knowledge Affect Economic Growth? - Lestari, Etty Puji; Caroline; Rahayu, Heffi Christya (CV ODIS, 2025)
Policy on restricting community activities at this time of the pandemic has made entrepreneurs make breakthrough innovations through online sales using the internet. Entrepreneurship spillover knowledge through the internet when selling their business. The purpose of this study is to analyze entrepreneurship and its effect on the economic growth of Central Java. This study adopts Romer's endogenous economic growth model using the Manhattan Distance spatial weight matrix with K-Near Neighbor to calculate LISA and the scatter plot matrix. The study results show the role of self-employed vocational graduates or workers undertaking entrepreneurial efforts in Central Java Province as Micro, Small, and Medium Enterprises (MSMEs). Vocational graduates have a stock of knowledge to share with others in the form of spillover technology for internet use in online sales. Internet use during the pandemic in Central Java Province, especially in online sales in the food and beverage industry, is dominant. The restricting social activities and the work-from-home policy encourage people to make transactions to sell goods or services and purchase goods or services online.